Survey of Heterodera glycines population abundance and virulence phenotypes during 2021-2022 in Heilongjiang Province - You, Jia; Wang, Jiajun; Tian, Runze; Wang, Siru; Yu, Ying; Xu, Lijian; Zhou, Changjun; Pan, Fengjuan; Chen, Jingsheng; Sui, Yueyu; Hu, Yanfeng (Plant disease, 2024)
Soybean cyst nematode (SCN), , poses a significant threat to global soybean production. Heilongjiang, the largest soybean-producing province in China, contributes over 40% to the country's total yield. This province has much longer history of SCN infestation. To assess the current situation in Heilongjiang, we conducted a survey to determine the SCN population density and virulence phenotypes during 2021-2022 and compared the data with a previous study in 2015. A total of 377 soil samples from 48 counties representing eleven major soybean-planting regions were collected. The prevalence of SCN increased from 55.4% in 2015 to 59% in the current survey. The population densities ranged from 80 to 26,700 eggs and juveniles per 100 cm3 of soil. Virulence phenotypes were evaluated for 60 representative SCN populations using the HG type test, revealing nine different HG types. The most common virulence phenotypes were HG types 7 and 0, accounting for 56.7% and 20% of all SCN populations, respectively. The prevalence of populations with a reproductive index (FI) greater than 10% on PI548316 increased from 64.5% in 2015 to 71.7%. However, the FI on the commonly used resistance sources PI 548402 (Peking) and PI 437654 remained low at 3.3%. These findings highlight the increasing prevalence and changing virulence phenotypes of SCN in Heilongjiang. They also emphasize the importance of rotating soybean varieties with different resistance sources and urgently identifying new sources of resistance to combat SCN.